Kemasaman Tanah, C-Mikroorganisme dan Pertumbuhan Bawang Daun di Lahan Gambut Berdasarkan Perbedaan Jarak Dari Saluran Air: Soil Acidity, C-Microorganisms and Spring Onion Growth in Peatlands Based on Different Distances from Waterways - Muhammad Daud Maulidi; Ahmad Kurnain; Abdul Hadi (Acta Solum, 2025)
This research aims to determine differences in soil acidity, C-microorganisms and the growth of spring onion (Allium fistulosum L.) on peatlands based on the difference in distance from waterways. The study will be conducted from February 2022 to May 2022. The implementation of the research is located in the Greenhouse and in the Laboratory of Physical Chemistry and Biology, Department of Soil Science, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. This research method is quantitative research with a survey approach using exploratory descriptive methods. The data analysis used was by paired T-Test analysis to find out the differences in parameters observed over a period of five days. The result of this study was that there was a difference in soil acidity and growth of spring onion plants, while C-microorganisms was not.